The influence of the socio-demographic factors on curriculum discrepancy for vocational skills training in folk development colleges in Tanzania - Frenk Josephat; Rose Ephraim Matete; Fortunata Kapasy Pembe (Освітній вимір, 2025)
This study investigated the influence of the socio-demographic factors on the discrepancy in vocational skills (VSs) curricula in folk development colleges (FDCs) in Tanzania. Utilising a mixed-methods research approach and correlational design, data were collected from 468 participants, including 384 students, 21 tutors, 58 FDC graduates and two (2) industry officials and were analysed by chi-square test and multivariate binary logistic regression. The results reveal significant associations between the socio-demographic characteristics and curriculum discrepancies. The results also indicate a lack of media exposure and absence of prior knowledge about vocational programmes that exacerbated the gap in skills attainment. Moreover, the results reveal that most students were young males from rural backgrounds, reflecting broader socio-economic challenges. The results further suggest that electrical installations, plumbing, and pipe-fitting had higher student participation than tailoring, although the statistical significance remained marginal. However, the results indicate no significant associations between age, gender, or place of residence and the discrepancies in VSs. The key argument in this study is that there is a need for targeted interventions that enhance media access and prior knowledge to better align VSs training with labour market demands. By addressing the identified gaps, VSs training institutions can improve educational outcomes and better meet the needs of diverse learner populations.